KINERJA LINGKUNGAN TERHADAP RETURN ON ASSET MELALUI CORPORATE SOCIAL RESPONSIBILITY DISCLOURE - Nurika Restuningdiah (Jurnal Keuangan dan Perbankan, 2010)
The purpose of this research was to examine the impact of environmental perfor-mance to Corporate Social Responsibility (CSR) disclosure, the impact of CSR disclosure toReturn on Asset, and the undirect impact of of environmental performance to Return onAsset through CSR disclosure. Path Analysis of 18 public companies listed in Indonesia StockExchange and participated in the Proper Program from 2007 -2008 through a judgment sam-pling technique indicated that environmental performance had a positive effect to Corpo-rate Social Responsibility (CSR) disclosure. The CSR disclosure had the positive impact toReturn on Asset, but the environmental performance had a negative effect to Return onAsset. This study also showed that there was positive undirect impact of environmentalperformance to Return on Asset through CSR disclosure. The implication of this study wasrelevant for public companies to publish their environmental performance on their annualreport (CSR Disclosure) in order to give the good news to the public, and get the goodimage to increase sales.